Design validation and simulation of Wells turbine blades - Aquino, Inno Jose Dominador C. (Animo Repository, 2021)
The use of non-renewable sources has been an arising problem globally, as they are inexpensive to extract but on the other hand, the use of these sources is continuously damaging the environment despite its scarcity. Fortunately, wave energy is one of the most abundant sources of energy in the Philippines. Although, there are many ways to use renewable energy such as the wind energy and solar energy, it is quite expensive for the average Filipino. To address this concern, the researchers designed blades of a Wells turbine to harness wave energy using six different types of blades namely, Reference Blade, Reference Blade Radiused Edge Tip, fx71|150, NACA0012, NACA0015, NACA0015 Radiused Edge Tip. These blades produced a power output of 0.19703kW, 0.18841kW, 0.21343kW, 0.21737kW, 0.23023kW, 0.2196kW respectively with a maximum turbine efficiency of 48.94345 percent attained by NACA00015. The proponents utilized the program SOLIDWORKS and ANSYS to validate the simulation. It was observed that former systems can be improved by modifying some specifications and repositioning the turbine. The researchers improved the design by placing the turbine in the middle of the casing which is 150 cm in length. This is done to have a fully developed flow upon reaching the turbine thereby increasing the power output of the system.